Reshaping Prognosis: Atrial fibrillation ablation in a case of severe tachycardiomyopathy in a young patient - Matei Diana-Cristina; Nistor Zamfira-Claudia; Burcin Alexandru Paul; Dragotoiu Nic Claudiu; Mandeş Leonard Alexandru; Antohi Elena Laura; Sipos Sergiu-Nicolae (Sciendo, 2024)
Tachycardiomyopathy, characterized by ventricular systolic dysfunction resulting from persistent tachycardia, poses a significant challenge in cardiovascular disease management. This article presents the case of a 31-year-old male patient with dilated cardiomyopathy and recurrent persistent atrial fibrillation, admitted due to heart failure decompensation. Ischemic and inflammatory etiologies for heart failure were ruled out in prior assessments. Despite multiple antiarrhythmic drugs and attempted electrical cardioversion, sinus rhythm was not maintained. Echocardiography confirmed a decline in the already reduced ejection fraction. Atrial fibrillation cryoablation was performed, and procedural specifics are detailed. Subsequent follow-up visits revealed a noteworthy improvement in exercise tolerance and ventricular function. This case underscores the importance of considering tachycardiomyopathy in the differential diagnosis of new-onset or worsening heart failure and highlights the potential for symptom resolution and ventricular function recovery with atrial fibrillation ablation.